The role of Commonwealth of Independent States (CIS) in the economic integration and political stability of the region - Malgorzata Runiewicz; Hanna Antonova (Transformation, Integration and Globalization Economic Research (TIGER), 2006)
The collapse of the Soviet Union revealed big productivity, structural and technological gaps between between its economy and Western markets. The latter made it difficult to reorient its members trade flows towards new Western and Asian markets. An alternative solution was to rebuild up intra-regional relations on new sound economic grounds. In 1991 twelve former Soviet Union republics (excluding the Baltic States) signed the agreement on the Commonwealth of Independent States (CIS). The CIS member countries have also signed a number of regional agreements including the bilateral agreements among the members. Regional integration agreements haven`t been that successful in the CIS as they were in the case of the CEE countries integration with the EU. The economic gains, in terms of shifting in the structure export specialization and intra-regional capital flows were very modest and could be applied only to several countries, with leading role of Russia. The last years of 2000-2005 show to a continuous growth for the whole CIS grouping and in particularly in Azerbaijan, Kazakhstan and Russia. The engine of this economic recovery results from the buoyant energy and metals prices as well as a strong domestic demand of its members. From the political perspective, the CIS played an important role of a regular interstate consultative forum, which had a positive effect on political stability in the region. On the other hand, multiple problems that arise in the work of the CIS restrain the organization from being effective in military conflict resolutions. In order to contribute from all the economic advantages offered by the regional integration CIS members have to face a challenge of creating new integration mechanisms. The latter mechanism must consider specific needs of CIS members and be evaluated on their individual merits integration policies. Moreover, the progress and benefits from the regional integration will depend on the sound domestic policies, good investment climate, basic property rights and infrastructure development.
Keywords: 330; Wirtschaftsintegration; Internationale Wirtschaftsbeziehungen; Auslandsinvestition; GUS-Staaten; Politische Instabilität